Simultaneous and continuous stabilization of As and Cd in contaminated soil by a half wrapping-structured amendment. Issue 4 (August 2021) - Shan, Danna; Shi, Yan; Zhou, Bin; Liu, Zilin; Yang, Liu; Zhu, Xuetao; Luo, Qishi; Li, Guanghe
Abstract: A simple and convenient method was used to prepare a novel granular half wrapping-structured amendment (HWA) for stabilization of both cationic and anionic heavy metals. By coating Ca(OH)2 with silicate minerals to obtain the core-coating wrapping balls, followed by drying and mixing with FeSO4, the final HWA effectively prevented the reaction of FeSO4 with Ca(OH)2 and exihibited high stabilization of arsenic (As) and cadmium (Cd) in the contaminated soils simultaneously and continuously. XRD, FTIR and SEM characterization showed that Ca(OH)2 was successfully wrapped by zeolite without changing their chemical properties. The amendment illustrated relatively fast stabilization for As and Cd, and the stabilization rate by HMA prepared at FeSO4 ·7H2 O: zeolite: Ca(OH)2 = 6.5:1:1 was 95.5% for As and 94.6% for Cd, much higher than the compound material (CM) which had side effect on Cd stabilization. In the effect of storage time experiment, when HWA was stored from 0 day to 365 days, the stabilization rate of As and Cd by HWA just decreased 3.4% and 4.3%, respectively. While the addition of CM to the soil reduced the As stabilization rate from 91.1% to 87.1% and the Cd stabilization rate was reduced from −139.8% to −223.1%. The long-term soil stabilization study demonstrated that HWA could decrease the concentration of extricable As and Cd simultaneously and continuously for 365 days without notable changes in soil pH. This research develops an easy method to synthesize granular HWA for the stabilization of cationic and anionic heavy metals from the actual contaminated soils. Graphical Abstract: ga1 Highlights: HWA is prepared by a novel half wrapping technique. HWA exhibits enhanced high stabilization rate for both As and Cd. HWA keeps high stabilization ability when stored up to 365 days. HWA can stabilize As and Cd simultaneously and continuously for a year.